Leveraging an open access platform to provide organizational value in clinical environments - Aida Marissa Smith; Alexia Estabrook; Mary Hyde; Michele Matucheski; Eleanor Shanklin Truex (Journal of the Medical Library Association)
The Ascension Nurse Author Index is an example of how resource-limited clinical libraries can provide value to their organization by creating a database of peer-reviewed journal article publications authored by their nursing associates. In 2024, Ascension launched a database index to highlight its nurse authors, bring attention to subject matter expertise, foster collaboration among authors, and recognize impact within the profession. The index uses an open access platform, software intended for reference management with a public-facing cloud option, to minimize expenses. This unconventional use of the platform allowed us to capitalize on the software's bibliographic database management capabilities while allowing us to input institutional-specific metadata. By creative use of the open-access platform, librarians can successfully partner to create value for their organization by highlighting the work of its nurses.